Predictors of perinatal mortality in emerging regions of Ethiopia: Evidence from EDHS 2016 - Fikreab Desta; Girma Beressa; Biniyam Sahiledengle; Telila Mesfin; Lemlem Daniel Baffa; Yordanos Sintayehu; Demisu Zenbaba; Daniel Atlaw; Lillian Mwanri (PLoS ONE, 2025)
Background Perinatal mortality rate is one of indictors used to measure the quality of obstetric and pediatric services globally. Compared to developed settings, perinatal mortality rate is higher in low-income countries, indicating societal inequities in health care and a scarcity of prenatal services. It is responsible for roughly 42% of all stillbirth in Sub-Saharan Africa, and 41% of newborn death globally. Despite Ethiopia’s efforts to reduce perinatal mortality by improving the quality of care for maternal and child health, perinatal mortality rate is still very high, and as to our search of pieces of literature there is no study in Emerging regions of the country. Therefore, this study aimed to assess the factors that contribute to perinatal mortality rate in emerging region (Afar, Gambela, Somali, and Benishangul Gumuz) of Ethiopia’s. Methods This study relied on data from the 2016 Ethiopian Demographic and Health Survey (EDHS). The analysis included the outcomes of 4, 070 pregnancies with a gestational age of 7 months or more. A multi-level mixed logistic regression analysis was used to examine individual and community-level predictors, accounting for the data’s hierarchical structure. A statistically significant association was determined with a p-value of ≤ 0.05. Results Of the 4,070 (weighted) pregnancies in total, 432 (57.36%) children were born to women with a mean age of 28.68 ± 6.53 (ages ± SD). The overall perinatal mortality rate in emerging regions of Ethiopia was 36 deaths per 1,000 pregnancies. The study found that having a birth interval < 2 years (AOR = 3.2, 95% CI: 1.51, 6.59), maternal age greater than or equal to 35 (AOR = 4.3, 95% CI: 1.84, 10.14), drinking an unimproved water source (AOR = 2.7, 95% CI: 1.14, 6.27), and mothers with no education (AOR = 0.33, 95% CI: 0.13, 0.86) were factors significantly associated with a high odds of perinatal mortality rate. Conclusion This study revealed a higher perinatal mortality rate as compared to national average. Maternal age, drinking an unimproved water source, and birth interval were significantly associated with perinatal deaths. Despite the enhanced effort to improve maternal and child services, there is still a need for more attention to these interconnected issues helps to reduce effectively the perinatal mortality rate in emerging regions of Ethiopia. Future researchers may benefit from focusing on strong study designs to investigate further the determinants of perinatal mortality, and policymakers good to pay special attention to incorporating the findings into policy.